Odpowiedzi

2009-09-13T14:24:00+02:00
A(2-b)+b³+(a+b)² dla a= -2 b= -3

-2(2-(-3))+(-3)²+(-2+(-3))²=-2*5+9+25=-10+34=24


3(a²-b²)-4a-4b dla a= -0,5 b=0,1
3(-0,5²-0,1²)-4*-0,5-4*-0,1=
3*(-0,25-0,01)+2+0,4= 3*(-0,26)+2+0,4=1,62
2009-09-13T14:27:57+02:00
A(2-b)+b³+(a+b)² dla a= -2 b= -3

2a-2b+b³+(a+b)²=2×(-2)-2(-3)+(-3)³+(-2-3)²=-4+6-27+(-5)²=2-27+25=0

3(a²-b²)-4a-4b dla a= -0,5 b=0,1

3a²-3b²-4a-4b=3(-0,5)²-3(0,1)²-4(-0,5)-4(0,1)=3×0,25-3×0,01+2-0,4=0,75-0,03+2-0,4=
2,75-0,43=2,32
Najlepsza Odpowiedź!
2009-09-13T14:30:02+02:00
A(2-b)+b³+(a+b)² =
=2a-ab+b³+a²+2ab+b²=
=2*(-2)-(-2)*(-3)+(-3)³+(-2)²+2*(-2)*(-3)+(-3)²=
=-4-6-27+2+12+9= -14.

3(a²-b²)-4a-4b=
=3a²-3b²-4a-4b=
=3*(-0,5)²-3*(0,1)²-4*(-0,5)-4*0,1=
=0,75-0,03+2-0,4= 2,32.